The Effect of Air-Water-Plasma-Jet-Activated Water on Penicillium: The Reaction of HNO2 and H2O2 Under Acidic Condition - Liu, Kun; Liu, Shi-ting; Ran, Cong-fu (Frontiers in Physics, 2020)
Plasma-activated water (PAW) that is produced by micro hollow cathode discharge (MHCD), where air is the working gas used. The treatment effect of PAW against Penicillium is expressed by the germination inhibition rate and the sporoderm-breakage rate. The maximum values of the germination inhibition rate and the sporoderm-breakage rate are 82.31% and 66.91%, respectively. In this paper, the importance of the reaction of HNO2 and H2O2, and its product ONOOH in Penicillium inactivation is illustrated. The substantial impact of ONOOH on inactivation beyond the theoretical lifetime is analyzed, and the complexity of peroxynitrite chemistry is responsible for prolonging this effect. Moreover, according to the reaction of HNO2 and H2O2 under acidic conditions, we identify a method for increasing the yield of ONOOH, namely, adding water into the working gas, which further contributes to the improvement of the treatment efficiency.